2017
DOI: 10.1016/j.sjbs.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Margin based ontology sparse vector learning algorithm and applied in biology science

Abstract: In biology field, the ontology application relates to a large amount of genetic information and chemical information of molecular structure, which makes knowledge of ontology concepts convey much information. Therefore, in mathematical notation, the dimension of vector which corresponds to the ontology concept is often very large, and thus improves the higher requirements of ontology algorithm. Under this background, we consider the designing of ontology sparse vector algorithm and application in biology. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 30 publications
(31 reference statements)
3
28
0
Order By: Relevance
“…Yang et al (2014) finds that the maximum removal efficiency of the composites for Cu 2+ was to 77.12% after 16 days of cultivation. The result of other studies was consistent with that result and showed there were about 77%-98% removal rate of Cu 2+ in wastewater (Gao et al 2017, Guerrini et al 2018, Deptuch et al 2011, Lu et al 2018). On the other hand, SRB are anaerobic microbes and have different vertical distributions at different depths (Jiang et al 2009, Kondo et al 2012, He et al 2015, Mogensen et al 2005, Gu and Zhang 2018.…”
Section: Introductionsupporting
confidence: 83%
“…Yang et al (2014) finds that the maximum removal efficiency of the composites for Cu 2+ was to 77.12% after 16 days of cultivation. The result of other studies was consistent with that result and showed there were about 77%-98% removal rate of Cu 2+ in wastewater (Gao et al 2017, Guerrini et al 2018, Deptuch et al 2011, Lu et al 2018). On the other hand, SRB are anaerobic microbes and have different vertical distributions at different depths (Jiang et al 2009, Kondo et al 2012, He et al 2015, Mogensen et al 2005, Gu and Zhang 2018.…”
Section: Introductionsupporting
confidence: 83%
“…The environment of deep confined water in this regional is closed well. In the reductive environment, under the effect of sulfate reducing bacteria and thermodynamic factors, H 2 S is likely to come into being if it experiences the effect of Bacterial Sulfate Reduction (BSR) or Thermochemical Sulfate Reduction (TSR) (Smith and Philips 1990, Manzano et al 1997, Mingju et al 2012, Machel 2001, Cross et al 2004, He et al 2016, Gao et al 2017, Li et al 2018, Estrada et al 2018, Ahamed et al 2017, Poppenga and Worstell 2016. Its possible reaction formula is shown in formula (1) to formula (4).…”
Section: The Control Effect Of Hydrological Characteristicsmentioning
confidence: 99%
“…Traditional fullerene is an all-carbon particle in which the iotas are masterminded on a pseudospherical structure made up altogether of pentagons and hexagons. Its subatomic diagram is a finite trivalent chart installed on the [17,18,[28][29][30][31][32][33].…”
Section: Carbon Nanotube Networkmentioning
confidence: 99%